Business Opportunities in India for Polish Entrepreneurs - Oskar Patnaik (Entrepreneurial Business and Economics Review)
The objective of this paper is to evaluate attractiveness of Indian market and to assess the gap between potential profit opportunities and the current value of Polish exports to India. The originality of this work lies in in-depth analysis of key aspects of Polish investment on Indian market, revealing the conservative attitude of Polish entrepreneurs towards Indo-Polish trade cooperation.